Formation of a multilevel system of human capital measurement indicators - Voloshyna, Svitlana (Technology audit and production reserves, 2018)
The object of research is human capital measurement. Acting as the initial stage of managing this capital, the measurement process in its current form is characterized by the presence of significant scientific gaps. Among the basic – a narrow range of elements of human capital for measurement, limited characteristics for individual elements of capital, the choice of the latter without proper justification, the identification of measurement and evaluation processes is similar. It is established that the preservation of these gaps threatens business by adopting unjustified managerial decisions, which will result in slowing the development of human capital with deteriorating quality characteristics or even its loss. The necessity of a clear delineation of the content and results of measurement and evaluation of human capital as adjacent processes of a single management contour is determined. Classification of indicators of measurement of the human capital of the enterprise is presented, in a complex reflects tasks of the given process and demands formation of system of corresponding indicators. The requirements for the system of indicators of measuring the human capital of an enterprise and its level are determined, and they correspond to the stages of reproduction of this capital. The expediency of distinguishing separate subsystems according to the elements of the human capital of the enterprise and the means of ensuring the functioning of these subsystems is proved, corresponds to the architectonics of the given capital and to the objects of administrative influence. The validity of the subsystems of measuring the human capital of an enterprise based on the elements «education capital», «promotion capital», «mobility capital», «health capital», «culture capital» and in terms of means of ensuring the functioning of the marked elements is justified. The procedure for measuring the human capital of an enterprise based on complex and general indicators of its status and indicators of its effectiveness is proposed. Realization of the developed proposals in practice allows to identify consistently and in-depth the state of the human capital of the enterprise, the development of means for ensuring the functioning of its individual subsystems, and the effectiveness of the use of aggregate human capital. Unlike similar known methods, approaches are proposed that provide the basis for further comprehensive assessment of both the characteristics of human capital and the levers of its management.